1996
DOI: 10.1007/s004240050119
|View full text |Cite
|
Sign up to set email alerts
|

Effect of stretch on calcium channel currents recorded from the antral circular myocytes of guinea-pig stomach

Abstract: The effect of membrane stretch on voltage-activated Ba2+ current (IBa) was studied in antral circular myocytes of guinea-pig using the whole- cell patch-clamp technique. The changes in cell volume were elicited by superfusing the myocytes with anisosmotic solutions. Hyposmotic superfusate (202 mosmol/l) induced cell swelling and increased peak values of IBa at 0 mV (from -406.6 +/- 45.5 pA to -547.5 +/- 65.6 pA, mean +/- SEM, n = 8) and hyperosmotic superfusate (350 mosmol/l) induced cell shrinkage and decreas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
32
1

Year Published

1997
1997
2014
2014

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 25 publications
2
32
1
Order By: Relevance
“…The latter current is very similar in duration. It is a hyposmotic swelling-induced increase of L-type calcium currents [14]. Thus I K(Ca) may play an important role in regulating cell tone in antral circular myocytes during hyposmotic conditions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The latter current is very similar in duration. It is a hyposmotic swelling-induced increase of L-type calcium currents [14]. Thus I K(Ca) may play an important role in regulating cell tone in antral circular myocytes during hyposmotic conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Other experiments have shown that I K(Ca) is activated by an intracellular Ca 2ϩ signal that is released from intracellular calcium stores during RVD [13]. But the effect of hyposmotic swelling on I K(Ca) and the role of intracellular or extracellular Ca 2ϩ in gastric smooth muscle cells has not been investigated.In our previous study, we reported that the voltageoperated calcium current (I Ca ) was increased [14] and that the volume-sensitive chloride current (I Cl ) was activated by hyposmotic swelling [15] in gastric antral myocytes of the guinea-pig. In the present study, we Key words: gastric smooth muscle cell, Ca 2ϩ -activated K ϩ current, Ca 2ϩ -induced Ca 2ϩ release, swelling.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In vascular and cardiac myocytes, cell shrinkage or swelling in hyper-or hyposmotic media has been reported to increase or decrease I Ca , respectively (Langton, 1993;Matsuda et al 1996;Xu et al 1996). Possibly, augmentation of I Ca by cell swelling is mediated by an increased mechanical strain from the cytoskeleton to the Ca 2+ channel protein.…”
Section: Implications For a Physiological Role Of F-actin Modulation mentioning
confidence: 99%
“…In our previous study, AA and other unsaturated fatty acids directly inhibited calcium currents [12] and muscarinic currents [13] . For both AA and hyposmotic membrane stretch-activated I K(Ca) [14,15] , activation by hyposmotic membrane stretch is associated with calcium-induced calcium release (CICR) [16] , which is triggered by extracellular calcium influx through the stretch-activated channels (SAC) in gastric antral circular myocytes of the guinea pig.…”
Section: Introductionmentioning
confidence: 99%